Insight into the role of stress response and toxic mechanism induced by Chloro-haloacetonitrile in vitro - Dong Li; Wen Cheng; Xiaoping Zhou; Xing Zheng; Jiehui Ren; Ting Meng (Ecotoxicology and Environmental Safety)
Chloro-haloacetonitrile (Cl-HAN), belongs to a group of nitrogenous disinfection by-products (N-DBPs) found in surface water, and are known to pose a major risk to the safety of human drinking water. However, the exact biological toxicity mechanism and the extent of the stress response caused by Cl-HAN remain unclear, resulting in a lack of effective measures to control its presence. Thus, the quantitative toxicological genomics and bioinformatics methods were applied to explore the effects of three chloro-haloacetonitriles (Cl-HANs) on the transcription of fusion genes under varying concentrations of stress in E. coli over 2-hour period. The initial stress response and their toxic mechanism were analyzed. The study also identified the molecular toxicity endpoint, and the core genes that are responsible for the specific toxicity of different Cl-HANs. Cl-HANs exhibited concentration-dependent characteristics of toxic effects, and caused changes in gene expression related oxidative and membrane stress. The stress response results showed that dichloroacetonitrile (dCAN) still caused significant DNA damage under the lowest concentration stress. Chloroacetonitrile (CAN) and trichloroacetonitrile (tCAN) exhibited lower genetic toxicity levels at 513 μg/L and 10.7 μg/L, respectively. The toxic effects of tCAN were widespread. And there was a good correlation between the molecular endpoint (EC-TELI1.5) and the phenotypic endpoint (LD50) with rp=-0.8634 (P=0.0593). In all concentrations of stress in CAN, dCAN, and tCAN, the number of overexpressed genes shared was 15, 2, and 14, respectively. Furthermore, bioinformatics analysis demonstrated that Cl-HANs affected genes associated with general stress pathways, such as cell biochemistry and physical homeostasis, resulting in changes in biological processes. And for CAN-induced DNA damage, polA played a dominant role, while katG, oxyR, and ahpC were the core genes involved in oxidative stress induced by dCAN and tCAN, respectively. These findings provide valuable data for the toxic effect of Cl-HANs.